Presidential Candidate Slogans in the 2024 Indonesian General Election; Strategic Communication with Multi-Generational Characteristics - Rozi, Romdhi Fatkhur (Eximia, 2023)
This study focuses on the use of slogans of the three presidential and vice-presidential candidates who will compete in Indonesia’s 2024 general election. This study maps how these slogans operate in the digital space of social media to capture the attention and votes of a cross-generational public in Indonesia. Discourse analysis is used in this study to discover the hidden meanings of texts, while taking into account the risk that these meanings may not be accurate. The researcher therefore limited the study to a specific time and space context, namely during the period leading up to the 2024 general election, and to an Indonesian case study only. The study found that slogans were chosen from popular diction, to make it easier to introduce the candidates’ profiles to the public. These slogans are also a special formula to shape public knowledge about the candidates’ vision and mission. This study holds the view that popularity and the massification process of promotional content still play an important role in the discourse distribution model in contemporary digital media. This connects the dialectic of discourse that occurs in a multi-generational society. In addition, this study also compares with the views of post-truth and post-factual politics with the assumption that the meaning generated from the use of slogans is not bound. Meaning is generated from highly subjective perceptions, so the role of promotion and massification of the chosen terminology still has an important role to influence audience perceptions and win votes from the active voting public.